Set-based design and optimisation of aircraft systems. - Georgiades, Alex (Cranfield University, 2018)
During the early stages of any system design, a thorough exploration of the design space can prove to be challenging and computationally expensive. The challenges are further exacerbated when dealing with complex systems, such as an aircraft, due to the high dimensionality of their design space. Arising from the Toyota Product Development System, Set-Based Design allows parallel evaluation of multiple alternative configurations in the early design stages. At the same time, optimisation methods can be employed at later stages to finetune the engineering characteristics of design, or architecture, variants. As part of this project, the ADOPT framework has been developed that integrates the aforementioned areas. This allows for a thorough exploration of the design space while ensuring the optimality of the selected designs. Furthermore, assessment methods are introduced to evaluate, not only the performance of each architecture variant, but also its sensitivity to design changes and the costs associated with them. Different visualisation tools are employed, including matrix methods and parallel coordinates, to act as design decision making mechanisms. Due to the wealth of information that such an approach generates, traceability of each architecture variant is also taken into consideration, and the knowledge acquired can be used for future design projects. The framework has been developed using a process-independent and tool-agnostic approach so that it can be applied to the design process of varying kinds of systems. To demonstrate the implementation and potential benefits, the framework has been applied to the design of a generic aircraft fuel system. The results from the case study and the framework itself are discussed, with a number of areas for further development and future work being identified and presented.
Keywords: Set-based design; optimisation; systems engineering; engineering design; visualisation; aircraft fuel systems